Evaluation of isosorbide-5-mononitrate as a cervical ripening agent prior to induced abortion in contrast to misoprostol- a randomized controlled trial - Aloke Kumar De; Bhattacharyya Sanjoy Kumar; Aparna Chakraborty; Amrita Samanta (Korean Society of Obstetrics and Gynecology, 2019)
ObjectiveTo determine whether vaginal application of 40 mg isosorbide-5-mononitrate (ISMN) has a comparable cervical ripening efficacy to and lesser side effects than 400 µg misoprostol in women scheduled for the first trimester induced abortion using a manual vacuum aspirator (MVA).MethodsWe conducted a prospective randomized open-label study in 70 women at 6-12 weeks of pregnancy at the R G Kar Medical College and Hospital, Kolkata, India, over a period of two years from 2015 to 2017. Forty milligrams of ISMN and 400 µg misoprostol were vaginally applied for cervical priming. The primary outcome measure was the cervical response assessed by the passage of the appropriate and largest sized MVA cannula through the internal os without resistance, at the beginning of the procedure.ResultsThe base line cervical dilatation was found to be significantly higher in the misoprostol group than in the ISMN group (7.65±1.38 vs. 6.9±1.26 mm; P=0.025, 95% confidence interval, −1.4046 to −0.953). However, when the women were sub-analyzed based on parity, there was no statistically significant difference in the same parameters among the multigravid women. The need for further cervical dilatation was significantly higher in the ISMN group when the primigravid women were compared, although the multigravid women responded favorably to ISMN.ConclusionIn the primigravid women, misoprostol appears to exert a higher efficacy as a cervical ripening agent in contrast to ISMN. However, ISMN can be used in multigravid women for the same purpose as in this group, misoprostol did not show any significant improvement in efficacy over ISMN.